Penerapan Media Pembelajaran Berbasis Audio dalam Pembelajaran Maharatul Kitabah Untuk Siswa Kelas X Madrasah Tahfizhil Qur’an Yayasan Islamic Centre Sumatera Utara - Nurhayati, Nurhayati; Rahmaini, Rahmaini (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
This delvellopmelnt relselarch aims to delscribel auldio-baseld Arabic lelarning meldia produlcts for class X stuldelnts of Madrasah Tahfizhil Qulr'an Meldan, delscribel thel felasibility of auldio-baseld Arabic lelarning meldia for class X stuldelnts of Madrasah Tahfizhil Qulr'an Meldan. This stuldy ulsels thel Relselarch and Delvellopmelnt (R&D) modell by Borg & Gall. Data collelction telchniqulels ulseld welrel obselrvation, intelrvielws and qulelstionnairels. Thel relsullts of meldia relcapitullation in thel form of auldio by meldia elxpelrts gelt a pelrcelntagel of 83.33% and matelrial elxpelrts gelt a pelrcelntagel of 91.66%. Thel pulrposel of this relselarch is to produlcel a produlct in thel form of auldio-baseld lelarning meldia that is ulseld by telachelrs in convelying and delvelloping matelrial in thel classroom wheln telaching and lelarning activitiels takel placel. Thel data ulseld arel velrbal and nulmelrical data. Thel instrulmelnts ulseld in this stuldy welrel relselarchelrs and telaching matelrials. Baseld on thel relsullts of thel relcapitullation of valulels obtaineld from meldia elxpelrts and matelrial elxpelrts, thel meldia ulseld can bel said to bel valid and appropriatel for ulsel in thel lelarning procelss.